Ca II Triplet Spectroscopy of Giants in Small Magellanic Cloud Star Clusters: Abundances, Velocities, and the Age-Metallicity Relation - Da Costa, G. S.; Hatzidimitriou, D. (1998)
We have obtained spectra at the Ca ii triplet of individual red giants in seven Small Magellanic Cloud (SMC) star clusters whose ages range from ~4 to 12 Gyr. The spectra have been used to determine mean abundances for six of the star clusters to a typical precision of 0.12 dex. When combined with existing data for other objects, the resulting SMC age-metallicity relation is generally consistent with that for a simple model of chemical evolution, scaled to the present-day SMC mean abundance and gas mass fraction. Two of the clusters (Lindsay 113 and NGC 339), however, have abundances that are ~0.5 dex lower than that expected from the mean age-metallicity relation. It is suggested that the formation of these clusters, which have ages of ~5 Gyr, may have involved the infall of unenriched gas, perhaps from the Magellanic Stream. The spectra also yield radial velocities for the seven clusters. The resulting velocity dispersion is 16 +/- 4 km s^-1, consistent with those of the SMC planetary nebula and carbon star populations.
Keywords: Astrophysics; GALAXIES: ABUNDANCES; GALAXIES: INDIVIDUAL: NAME: SMALL MAGELLANIC CLOUD; GALAXIES: KINEMATICS AND DYNAMICS; GALAXIES: MAGELLANIC CLOUDS; galaxies: star clusters